Psilocybin's Emerging Role in Combating Depressive Disorder - Anna Jaremek; Joanna Kępa; Norbert Kandefer; Michał Wyszkowski; Aleksandra Grabarczyk; Anna Pawlak; Sylwia Grad; Małgorzata Gregorek; Paweł Gregorek (Kazimierz Wielki University, 2023)
In this review paper, we delve into the potential applicability of psilocybin - a naturally synthesized psychedelic substance found within select species of fungi, as a prospective avenue for depression treatment. Depression, a widespread psychological malady affecting countless individuals across the globe, often proves stubborn against existing treatment modalities, necessitating exploration into new options. The spotlight has increasingly been cast on psilocybin, thanks to its promising therapeutic capacities for a spectrum of mental health disorders, notably including depression. This article dissects the operational mechanisms of psilocybin, referencing germane clinical trials, and weighing the prospective risks and rewards related to its usage. Pooled findings from an array of clinical studies hint at the possibility of psilocybin furnishing swift and lasting advantages for managing depression and similar disorders. Trial participants who underwent a combined regimen of psilocybin and psychotherapy recorded enduring alleviation in their anxiety and depressive symptoms. Psilocybin has been observed to trigger modifications in neural activity, predominantly in the brain's default mode network (DMN) and the prefrontal cortex (PFC). These alterations have been correlated with a decrease in self-oriented cognitive processes, an uptick in positive emotional states, and the facilitation of neuroplasticity. When compared with standard antidepressant medications, the symptomatic improvements seen with psilocybin were largely equivalent. Preclinical investigations have also underlined psilocybin's potential in augmenting neural plasticity and neurogenesis, thus hinting at its possible utility in the fields of neurosurgery and neurooncology.